Return on investment for pre-K and primary teacher training in meeting social-emotional and cognitive developmental needs - Schneider, Arthur Ernst (AUC Knowledge Fountain, 2015)
This thesis argues that since the social-emotional components of early childhood development and education augment cognitive development, holistic early childhood teacher training that prepares educators regarding both types of development would further improve the well-established return on investment seen as a result of health and wellness programs at pre-natal and pre-school stages.